Electromechanical properties of textured K0.5Na0.5NbO3 ceramics - Pinho, Rui Manuel de Oliveira (2015)
This work is about lead-free ceramic materials intended for electromechanical applications and candidates to replace lead-based electroceramics. One of the most widely used piezoelectric ceramics is lead zirconate titanate (PZT). However, it contains more than 60% of lead and it is toxic for humans and environment. In 2003, a directive from European Union has prohibited the use of potentially hazardous elements as lead. Due to the lack of competitive materials for PZT replacement an exception was created until a competitive alternative be found. Potassium and sodium niobate due to its high Curie temperature and moderate piezoelectric properties is currently one of the most promising lead-free materials for PZT substitution. However, its effective industrial adoption requires, among others, optimization of its properties. In this context, in this work we initially studied the effect of dopants, texturing and sintering temperature of KNN ceramics. For this purpose KNN ceramics doped with i) 1.5 mol% CuO + 2.0 mol% Li2O, ii) 1.5 mol% CuO + 4.0 mol% Li2O and iii) 1.5 mol% CuO + 0.5 mol% MnO using different sintering temperatures (1050, 1065 and 1080 °C) were prepared. In addition in order to maximize the preferential crystallographic orientation of the ceramic KNN (texturing), in this case in the direction (h00), KNN single crystals were produced. These crystals were used as seeds in the texturing process KNN ceramics. It was found that the composition doped with copper and manganese was the only single phase one of the studied compositions. Dense (> 95%) ceramics, textured and non-textured, and with a high Lotgering factor among the studied compositions (≈ 20%) were prepared. The dependence of the dielectric properties of the Lotgering factor was demonstrated. In the attempt to optimize the Lotgering factor to top up the piezoelectric properties, the effect of the quantity of added crystals, heating and cooling rate and duration of sintering cycle were studied for the composition doped with copper and manganese. To this end, KNN textured ceramics and doped with 1.5 mol% of CuO and 0.5 mol% MnO, using 2.5, 5.0 and 10.0 wt% of single crystals were processed. For the same composition the heating rate of 2 °C/min and 20 °C/min and sintering level between 4 and 24 h was varied. Dense single phase KNN ceramics with an increase in the Lotgering factor from ≈20% to ≈38% for KNN ceramics doped with 1.5 mol% of copper and 0.5 mol% of manganese, textured with 5 wt% crystals and sintered at 1065 °C for 24 h with a heating rate/cooling of 10 °C/min have been achieved. These ceramics exhibit a relative permittivity at room temperature ≈ 300 for a Curie temperature value which remained high (TC ≈ 400 °C). The piezoelectric coefficient increased (d33 = 65 pC/N) with increased texturing. Despite the value of the piezoelectric coefficient achieved is still modest, the obtained piezoelectric voltage constant revealed values (g33 = 23.9 * 10-3 Vm/N) comparable to the values reported for certain compositions of commercial PZT, showing clearly competitive opportunities in applications (such as piezoelectric sensors) for KNN ceramics. The results of this study definitely contribute to the knowledge in the field of lead-free piezoelectric materials.